PENGARUH DAU, JUMLAH PENDUDUK, IPM DAN BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI DI MALUKU UTARA - ERI SETYOWATI; RIFKI KHOIRUDIN (JURNAL ILMIAH SIMANTEK, 2022)
The results of the study partially show that, (1) the general allocation fund has no effect on economic growth, (2) thepopulation has a positive and significant effect on economic growth, (3) the human development index has a positive andsignificant effect on economic growth, (4 ) Capital expenditure has no effect on economic growth. While the results ofsimultaneous research, namely general allocation funds, population, human development index, and capital expendituressimultaneously have a significant influence on economic growth. Researchers took this title by looking at previousresearchers, one of which is research from Astria (2014) entitled "Analysis of the Effect of General Allocation Funds andCapital Expenditures on Economic Growth". The regression results show that general allocation funds have a negative andsignificant effect on economic growth, but capital expenditures have a positive and significant effect on economic growth.